Design and Tailoring of a Three-Dimensional Lithium Rich Layered Oxide-Graphene/Carbon Nanotubes Composite for Lithium-Ion Batteries. (1st September 2016) - Wang, Tao; Chen, Zhanjun; Zhao, Ruirui; Chen, Hongyu
Abstract: Poor rate capability and cycling performance are the major barriers to the application of lithium rich layered oxides as the next generation cathodes for lithium-ion batteries. In this paper, a novel tactics is applied to enhance the rate property and low temperature performance of lithium rich layered oxides materials by using graphene and multi-walled carbon nanotubes as the building blocks to form a hybrid 3D conductive network in the synthesized composites. Spray pyrolysis method is employed to obtain the target material. The hybrid 3D conductive network can decrease the reaction overpotential greatly, as well as reduce the cell resistance and enhance the lithium ion transportation in the bulk material, which are confirmed by cyclic voltammetry measurement and electrochemical impedance spectroscopy. The conductivity of the obtained composite is so high that no additional conductive agent is needed in the fabrication of electrodes. Our investigation further demonstrates that the conducting framework can efficiently alleviate the polarization of pristine lithium rich layered oxides material, leading to an outstanding enhancement in rate capability, low temperature performance and cycling stability.